Intergenerational comparisons in the uses and reasons for the use of ict in elderly and middle-aged people in an Argentine city - Tarditi, Liliana (2022)
Technologies constitute a challenge for the elderly and middle-aged as they require the acquisition of new knowledge to stay socially included. Objective: To determine the intergenerational differences in access, uses, intensity, frequency and variety of uses of ICT, as well as the reasons for their use. The research was applied, quantitative, descriptive and correlational, cross-sectional. An intentional, non-probabilistic sample of 157 adults was formed, who attend basic and advanced computer courses, of non-formal education for older adults in Río Cuarto, Argentina. Middle age groups were considered (50 to 64 years) n = 54, early old age (65 to 74 years) n = 84; and advanced old age (75 to 85 years) n = 22. The data were collected through self-administered questionnaires and the analysis was performed with the SPSS software. The findings show that the uses of ICTs, as well as their accessibility and intensity of use, show slight quantitative variations. The differences in the reasons why each group uses ICT are relevant. Past digital practices or everyday life, in addition to the motivations of the subjects, explain the variety of uses, rather than the generational imprint.